Keberlanjutan Kebun Kelapa Dalam (Cocos Nucifera) Blok Penghasil Tinggi di Kabupaten Tanjung Jabung Timur, Jambi - Asnelly Ridha Daulay; Araz Meilin (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2020)
Sustainability of the Cocos Nucifera’s High Production Block (HPB) in Tanjung Jabung Timur Regency. Jambi Province is threatened by falling coconut prices. It influences the farmer's interest to do replanting and use certified seeds produced by HPB. The evaluation of HPB not only base on the economic dimension, but it should also accommodate broader dimensions. The purpose of the study is to analyze the sustainability of HPB. Primary data were obtained from observations, focus group discussions, and interviews with 20 respondents of HPB plantation owners, while secondary data were obtained from Statistics office and government agencies. The existing condition of the HPB was analyzed by comparing it with the standard of HPB and selected parent trees issued by the Indonesian Ministry of Agriculture. Analyzing of HPB sustainability used a modified Multi-Dimensional Scaling (MDS) Rapfish for coconut, then called Rap-ProBlock (The Rapid Appraisal of the Status of Cocos Nucifera's High Producing Block). The results showed that the sustainability indexes were sufficient and good for the social (64.18) and ecological (85.69) dimensions, the economic and technological dimensions had less sustainability (34.76 and 32.58), and the legal/institutional dimension was poor (9. 16). On a multi-dimensional basis, HPB sustainability was lacked (40.30). The recommended policies based on this research results among others are i.e. issuing the Local Regulation on Cocos Nucifera, establishing the Warehouse Receipt System which guarantees farmers a fair price, and, involving village enterprise to build coconut business units.